Taking an aesthetic risk in management education: Reflections on an artistic-aesthetic approach. Issue 3 (July 2013) - Mack, Kathy
This article responds to calls from the field of organizational aesthetics to study and represent sensible-aesthetic knowledge with artistic-aesthetic approaches. An artistic-aesthetic touchstone artifact engages the sensibilities of 54 MBA Organizational Behavior students as they take an aesthetic risk to enjoy exploring and re-presenting the aesthetic dimension of group organizational life. In the context of dominant business school pedagogic practices that tend to neglect aesthetics, student reflections reveal that the creative process itself is imbued with its own aesthetic value. This study contributes to artistic-aesthetic knowing at the group level of understanding. This paper also makes a contribution to the field of organizational aesthetics by extending its reach into management education practices. It is further suggested that an aesthetic inquiry into the aesthetics of management education is well worth the effort. In accordance with aesthetic criteria, this paper seeks to represent a plausible account of this management education journey.